Escitalopram induced Tremors- A Rare Side Effect - Amatya, Richa (Annapurna Journal of Health Sciences, 2024)
Selective serotonin reuptake inhibitors (SSRIs) which includes escitalopram is used to treat various psychiatric disorders such as depression, anxiety, obsessive compulsive disorder and premenstrual dysphoric disorder. All SSRI’s have common pharmacological feature that is selective inhibition of serotonin reuptake. However, it can lead to various side effects among which tremors can occur as a drug induced movement disorder. Here, a case of escitalopram induced tremor has been described in patient who was being treated with the same for anxiety disorder. This case gives an insight on a way to move forward if patients develop tremors upon initiating SSRI to treat their underlying psychiatric condition.